Assessing the impact of pneumococcal conjugate vaccines on invasive pneumococcal disease using polymerase chain reaction-based surveillance: an experience from South Africa. Issue 1 (December 2015) - Tempia, Stefano; Wolter, Nicole; Cohen, Cheryl; Walaza, Sibongile; Mollendorf, Claire; Cohen, Adam; Moyes, Jocelyn; de Gouveia, Linda; Nzenze, Susan; Treurnicht, Florette; Venter, Marietjie; Groome, Michelle; et al.
Abstract Background The use of molecular diagnostic techniques for the evaluation of the impact of pneumococcal conjugate vaccines (PCVs) has not been documented. We aimed to evaluate the impact of PCVs on invasive pneumococcal disease (IPD) using polymerase chain reaction (PCR)-based techniques and compare with results obtained from culture-based methods. Methods We implemented two independent surveillance programs for IPD among individuals hospitalized at one large surveillance site in Soweto, South Africa during 2009–2012: (i) PCR-based (targeting thelytA gene) syndromic pneumonia surveillance; and (ii) culture-based laboratory surveillance. Positive samples were serotyped. The molecular serotyping assay included targets for 42 serotypes including all serotypes/serogroups included in the 7-valent (PCV-7) and 13-valent (PCV-13) PCV. The Quellung reaction was used for serotyping of culture-positive cases. We calculated the change in rates of IPD (lytA - or culture-positive) among HIV-uninfected children aged <2 years from the year of PCV-7 introduction (2009) to the post-vaccine years (2011 or 2012). Results During the study period there were 607lytA -positive and 1, 197 culture-positive cases that were serotyped. Samples withlytA cycle threshold (Ct)-values ≥35 (30.2 %; 123/407) were significantly less likely to have a serotype/serogroup detected for serotypes included in the molecular serotyping assay than those with Ct-values <35 (78.0 %; 156/200) (p  < 0.001). From 2009 to 2012 rates of PCV-7 serotypes/serogroups decreased −63.8 % (95 % CI: −79.3 % to −39.1 %) amonglytA -positive cases and −91.7 % (95 % CI: −98.8 % to −73.6 %) among culture-positive cases. Rates oflytA -positive non-vaccine serotypes/serogroups also significantly decreased (−71.7 %; 95 % CI: −81.1 % to −58.5 %) over the same period. Such decline was not observed among the culture-positive non-vaccine serotypes (1.2 %; 95 % CI: −96.7 % to 58.4 %). Conclusions Significant downward trends in IPD PCV-7 serotype-associated rates were observed among patients tested by PCR or culture methods; however trends of non-vaccine serotypes/serogroups differed between the two groups. Misclassifications of serotypes/serogroups, affecting the use of non-vaccine serotypes as a control group, may have occurred due to the low performance of the serotyping assay amonglytA -positive cases with high Ct-values. Until PCR methods improve further, culture methods should continue to be used to monitor the effects of PCV vaccination programs on IPD incidence.